Efforts to improve 3R literacy (reduce, reuse and recycle) in creating a healthy environment - Robiul Fitri Masithoh; Alpayana Cecylia Jisarah; Lutfi Nur Annisa; Muhammad Iqbal; Maulana Khakim; Farhan Azmi Ghani; Puspa Amalia Fajrin (Community Empowerment, 2021)
Waste is an inseparable impact of human activities, both the result of organisms or natural processes. Waste that is not managed properly will cause problems, especially those related to public health and environmental hygiene. The amount of garbage piled up every day is quite large and the majority comes from residential waste. Therefore, it is necessary to manage waste through 3R (Reduce, Reuse, and Recycle). However, the implementation of 3R activities in the community is still constrained, especially by the lack of public awareness to sort waste. The purpose of the community empowerment is to increase public health literacy through the 3R principles at the waste bank in Wonosuko Hamlet, Tegalrejo, Magelang. The method used in this community service activity is to use the Participatory Rural Appraisal (PRA) approach by socialization, training and mentoring. The results of this service activity indicate that after the training there was an increase in awareness in establishing a healthy environment by implementing 3R through a waste bank in the Wonosuko Hamlet, Tegalrejo, Magelang.